Placement of Posterior Composite Restorations: A Cross-Sectional Study of Dental Practitioners in Libya - Jedeh, Mohamed; Mohamed Ben Hakoma; Farouk Ben Fadl (Khalij-Libya Journal of Dental and Medical Research, 2024)
Dental practitioner-related factors can influence the quality and longevity of composite restorations. This study aimed to examine the clinical techniques used by dental practitioners (DPs) in Tripoli, Libya, when placing direct posterior composite restorations, with a focus on identifying any associations between clinical practices and years of experience. A questionnaire survey covering aspects of posterior composite placement, including material preference, cavity preparation, adhesive technique, isolation method, and occlusion adjustment, was distributed to 120 DPs in Tripoli. Data were statistically analyzed using Fisher’s exact test to assess associations between years of experience and specific clinical practices. Composite was the preferred material for both small and large posterior cavities across all experience levels. No statistically significant associations were found between years of experience and key clinical practices, including preparation techniques (pulpal depth, p = 0.9005), adhesive choice (p = 0.5679), isolation method (p = 0.2515), and occlusal adjustment (p = 0.7469). The study found that DPs in Tripoli display a standardized approach to posterior composite restorations, with minimal variation in clinical techniques based on experience. These findings suggest the effectiveness of foundational training in establishing consistent practices among Libyan DPs, though further emphasis on specific techniques, such as rubber dam isolation, may be beneficial in education and training. يمكن أن تؤثر العوامل المتعلقة بأطباء الأسنان على جودة وطول عمر ترميمات الكومبوزيت. هدفت هذه الدراسة إلى فحص التقنيات السريرية التي يستخدمها أطباء الأسنان في طرابلس، ليبيا، عند وضع ترميمات الكومبوزيت الخلفية المباشرة، مع التركيز على تحديد أي ارتباطات بين الممارسات السريرية وعدد سنوات الخبرة. الطرق: تم توزيع استبيان يغطي جوانب وضع الكومبوزيت الخلفي، بما في ذلك تفضيل المواد، تحضير التجاويف، تقنية اللصق، طرق العزل، وضبط الإطباق، على 120 طبيب أسنان في طرابلس. تم تحليل البيانات إحصائيًا باستخدام اختبار فيشر لتقييم الارتباطات بين سنوات الخبرة والممارسات السريرية المحددة. كانت مادة الكومبوزيت هي المادة المفضلة لكل من التجاويف الصغيرة والكبيرة الخلفية عبر جميع مستويات الخبرة. لم تُظهر النتائج أي ارتباطات إحصائية ذات دلالة بين عدد سنوات الخبرة والممارسات السريرية الرئيسية، بما في ذلك تقنيات التحضير (عمق اللب، p = 0.9005)، اختيار تقنية اللصق (p = 0.5679)، طريقة العزل (p = 0.2515)، وضبط الإطباق (p = 0.7469). أظهرت الدراسة أن أطباء الأسنان في طرابلس يتبعون نهجًا موحدًا في ترميمات الكومبوزيت الخلفية، مع وجود تباين بسيط في التقنيات السريرية بناءً على الخبرة. تشير هذه النتائج إلى فعالية التدريب الأساسي في تأسيس ممارسات متسقة بين أطباء الأسنان الليبيين، ومع ذلك قد يكون من المفيد تعزيز بعض التقنيات مثل استخدام عزل المطاط (Rubber Dam) في التعليم والتدريب